Penerapan Metode Ekspresi Bebas Untuk Meningkatkan Kreativitas Menggambar Anak Kelompok Bermain Usia 5-6 tahun - ., Lara Septaria; ., Retno Wulandari; ., Fahmi (CV. ITTC INDONESIA, 2023)
Kindergarten age is the age when children express themselves a lot through free expression to increase creativity in children. The focus of this research is to discuss the application of the free expression method to increase the creativity of drawing in playgroup children aged 5-6 years. The purpose of this study was to describe the application of the free expression method to increase the drawing creativity of playgroup children aged 5-6 years. The method used in this study is a qualitative method with an active research approach in the classroom. While the data used are primary data and secondary data. Primary data comes from student grades Secondary data is generated from peer observations. The results of the study that can be concluded are based on the results of the study it can be concluded that the free drawing method can increase children's creative efforts. This can be seen from the results of children's creativity at the pre-session stage before carrying out the procedure. Only 20% of children had creative abilities which increased to 40% in the first cycle and the level of mastery in the second cycle became 80%. From the data above it can be concluded that the free drawing method can increase the creativity of children in student play groups